Improving Body Immunity by Sporting Activities During the Covid-19 Pandemic - Lydia Meilani (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Covid-19 has changed the way people take care of their health, many people do sports activities to help increase their immune systems. Some sports criteria are good for maintaining or even increasing the body's immune system. The chosen sport needs to pay attention to its frequency, duration, consistency, and type. A strong immune system will help protect the body from viruses and diseases. Objectives: To find out the types of sports that are of interest to increase immunity. Results: The survey results show that 91% of respondents have a habit of exercising and the remaining 9% do not exercise. The types of exercise are 42% choose cycling, 25% morning run, 15% gymnastics, 5% brisk walking, and the remaining 4% mountain climbing, yoga, and swimming. Conclusion: The type of sports activity that Leuwiliang Hospital employees are interested in maintaining health is cycling, but it is necessary to pay attention to the duration, frequency, intensity, type, and consistency Suggestion: It is recommended for the public to do sports regularly by paying attention to the type of sports activity selection, duration, frequency, intensity to obtain the perfect conditions to increase the body's immunity, especially during the Covid-19 pandemic.